2019
DOI: 10.21608/jesp.2019.68181
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Multiple Staining Techniques for Identification of Different Developmental Stages of Acanthamoeba and Naegleria

Abstract: Potentially pathogenic free-living amoebae (FLA) are unique protozoa that present a healthcare challenge. The appropriate choice of staining technique is crucial to improving the efficiency of microscopic diagnosis of FLA isolated from environmental as well as clinical samples. This study aimed to evaluate different staining techniques for morphological identification of Acanthamoeba and Naegleria isolated from tap water samples in different localities in Assiut City, Egypt. A multi-attribute evaluation was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These include temporary wet mounts by iodine, eosin, methylene blue, lactophenol cotton blue, potassium hydroxide, and calcofluor white stain; and permanent staining of smears using Gram, Gimenez, Giemsa, chlorazol black, H and E, iron hematoxylin, periodic acid–Schiff, Masson's trichrome, Field's, Gomori's methenamine silver, and acridine orange stains. [ 14 15 ] The temporary wet mounts are simple, single-step, rapid, and inexpensive methods that have an added advantage of demonstrating the motility of the trophozoite forms. However, they are transient preparations; and therefore, may not be available for further review and evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include temporary wet mounts by iodine, eosin, methylene blue, lactophenol cotton blue, potassium hydroxide, and calcofluor white stain; and permanent staining of smears using Gram, Gimenez, Giemsa, chlorazol black, H and E, iron hematoxylin, periodic acid–Schiff, Masson's trichrome, Field's, Gomori's methenamine silver, and acridine orange stains. [ 14 15 ] The temporary wet mounts are simple, single-step, rapid, and inexpensive methods that have an added advantage of demonstrating the motility of the trophozoite forms. However, they are transient preparations; and therefore, may not be available for further review and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are transient preparations; and therefore, may not be available for further review and evaluation. [ 14 16 ] In Egypt, two large multi-attribute ranking analyses of different staining methods for the identification of morphological forms of Acanthamoeba were done in 2015 and 2019. Among the temporary mounts evaluated, it was found that the iodine wet mount was better than others; among permanent stains, Gimenez stain and Giemsa stain were found to be more effective in demonstrating morphological details.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation